2015
DOI: 10.1111/adb.12332
|View full text |Cite
|
Sign up to set email alerts
|

Altered white matter integrity in whole brain and segments of corpus callosum, in young social drinkers with binge drinking pattern

Abstract: Binge drinking is associated with impaired cognitive functioning, but the relationship of cognitive impairments and white matter integrity is less known. We used diffusion tensor imaging (DTI) to investigate the relationships of binge drinking, whole brain white matter integrity and cognitive performance during young adulthood (18 to 25 years), a period of continued brain development in two sessions 1 year apart. Binge drinkers (n = 20) and non-binge drinkers (n = 20) underwent DTI and completed measures of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 49 publications
2
40
2
2
Order By: Relevance
“…As described by Garg and colleagues (2015), the corpus callosum would be especially vulnerable to demyelination and inflammatory processes, which could reduce the intra-axonal compartment volume fraction in these regions. This region was already suggested to be vulnerable to toxicity earlier due to chemotherapy , but also due to alcohol abuse as well (Kapogiannis et al, 2012;Smith et al, 2017).…”
Section: Distinction Between Global and Local Differences In Fixel-mentioning
confidence: 99%
“…As described by Garg and colleagues (2015), the corpus callosum would be especially vulnerable to demyelination and inflammatory processes, which could reduce the intra-axonal compartment volume fraction in these regions. This region was already suggested to be vulnerable to toxicity earlier due to chemotherapy , but also due to alcohol abuse as well (Kapogiannis et al, 2012;Smith et al, 2017).…”
Section: Distinction Between Global and Local Differences In Fixel-mentioning
confidence: 99%
“…It is widely held that adolescent mammals are particularly sensitive to alcohol exposure, and that this sensitivity is especially severe when exposure is intermittent, such as occurs in humans with binge drinking (Smith et al . ; Stephens & Duka ). Recently, the Indiana group have reported a series of observations on altered gene expression (mRNA) in alcohol‐preferring P rats following three weeks consumption of alcohol in a ‘binge’ pattern, reaching blood levels of 100 mg/dL, over a period spanning postnatal days (PDs) 28–49 (McBride et al .…”
Section: Evidence For Gabaa Receptor Involvement In Addictionmentioning
confidence: 99%
“…We applied TBSS for determining microstructural differences between treatment-seeking alcohol-dependent individuals and light drinkers: FA was lower in fibers within frontal WM, limbic pathways, and between cortico-striatal regions; in the small group of patients, associations between drinking severity and regional FA were insignificant (Yeh et al, 2009). Other TBSS studies in alcohol dependence reported FA deficits specifically within cingulum, corpus callosum, fornix (Durkee et al, 2013; Trivedi et al, 2013; Pfefferbaum et al., 2014; Smith et al, 2015; Sorg et al, 2015), and superior longitudinal fasciculus (Pfefferbaum et al, 2014; Segobin et al, 2015). Microstructural abnormalities were most pronounced in major tracts within frontal WM (Fortier et al, 2014; Pfefferbaum et al, 2014; Sorg et al, 2015) and related to higher lifetime alcohol consumption (Sorg et al, 2015).…”
Section: Introductionmentioning
confidence: 95%